Bankruptcy And Restructuring of Entrepreneurs As Instruments Protecting The Creditor and Debtor In Poland - Anna OLKIEWICZ (Communications of International Proceedings, 2023)
The economic and political changes that took place in Poland after 1989, and in particular the transition from a planned economy system to a free market, caused a revival of these legal regulations, which before 1989 were of little importance. These areas include, in particular, bankruptcy and restructuring law. It lays down rules for the removal or restructuring of market participants who, for reasons attributable or not, have become insolvent. The article addresses an important problem concerning restructuring proceedings and bankruptcy of enterprises. This is an important issue for the economy, because the effectiveness of these proceedings has not only an economic dimension, but also a social one. The aim of the article is to deepen knowledge in the field of the above-mentioned proceedings in terms of their use by Polish entrepreneurs. Studies have shown that the number of restructurings is growing every year, while the number of bankruptcies of entrepreneurs in Poland is decreasing. This is related to the new and attractive changes in proceedings, especially for debtors, which protect the debtor's situation to a greater extent than before, giving him a chance to heal.
Keywords: finance; bankruptcy; restructuring; management; risk